Adolescent Motherhood and HIV in South Africa: Examining Prevalence of Common Mental Disorder - Roberts, K.J.; Smith, C.; Cluver, L.; Toska, E.; Zhou, S.; Boyes, Mark; Sherr, L. (SPRINGER/PLENUM PUBLISHERS, 2022)
The mental health of adolescents (10–19 years) remains an overlooked global health issue, particularly within the context of syndemic conditions such as HIV and pregnancy. Rates of pregnancy and HIV among adolescents within South Africa are some of the highest in the world. Experiencing pregnancy and living with HIV during adolescence have both been found to be associated with poor mental health within separate explorations. Yet, examinations of mental health among adolescents living with HIV who have experienced pregnancy/parenthood remain absent from the literature. As such, there exists no evidence-based policy or programming relating to mental health for this group. These analyses aim to identify the prevalence of probable common mental disorder among adolescent mothers and, among adolescents experiencing the syndemic of motherhood and HIV. Analyses utilise data from interviews undertaken with 723 female adolescents drawn from a prospective longitudinal cohort study of adolescents living with HIV (n = 1059) and a comparison group of adolescents without HIV (n = 467) undertaken within the Eastern Cape Province, South Africa. Detailed study questionnaires included validated and study specific measures relating to HIV, adolescent motherhood, and mental health. Four self-reported measures of mental health (depressive, anxiety, posttraumatic stress, and suicidality symptomology) were used to explore the concept of likely common mental disorder and mental health comorbidities (experiencing two or more common mental disorders concurrently). Chi-square tests (Fisher’s exact test, where appropriate) and Kruskal Wallis tests were used to assess differences in sample characteristics (inclusive of mental health status) according to HIV status and motherhood status. Logistic regression models were used to explore the cross-sectional associations between combined motherhood and HIV status and, likely common mental disorder/mental health comorbidities. 70.5% of participants were living with HIV and 15.2% were mothers. 8.4% were mothers living with HIV. A tenth (10.9%) of the sample were classified as reporting a probable common mental disorder and 2.8% as experiencing likely mental health comorbidities. Three core findings emerge: (1) poor mental health was elevated among adolescent mothers compared to never pregnant adolescents (measures of likely common mental disorder, mental health comorbidities, depressive, anxiety and suicidality symptoms), (2) prevalence of probable common mental disorder was highest among mothers living with HIV (23.0%) compared to other groups (Range:8.5–12.8%; Χ2 = 12.54, p = 0.006) and, (3) prevalence of probable mental health comorbidities was higher among mothers, regardless of HIV status (HIV & motherhood = 8.2%, No HIV & motherhood = 8.2%, Χ2 = 14.5, p = 0.002). Results identify higher mental health burden among adolescent mothers compared to never-pregnant adolescents, an increased prevalence of mental health burden among adolescent mothers living with HIV compared to other groups, and an elevated prevalence of mental health comorbidities among adolescent mothers irrespective of HIV status. These findings address a critical evidence gap, highlighting the commonality of mental health burden within the context of adolescent motherhood and HIV within South Africa as well as the urgent need for support and further research to ensure effective evidence-based programming is made available for this group. Existing antenatal, postnatal, and HIV care may provide an opportunity for mental health screening, monitoring, and referral.